26.7k views
5 votes
Question 22 of 25 If f(x) = -3x-5 and g(x) = 4x-2, find (f+g)(x). O A. (f+g)(x) = 7x-7 B. (f+g)(x) = x-7 O C. (P+ 9) (1,5 -7x-3 O D. (f+g)(x) = -x + 3

Question 22 of 25 If f(x) = -3x-5 and g(x) = 4x-2, find (f+g)(x). O A. (f+g)(x) = 7x-example-1
User Buzzet
by
5.3k points

1 Answer

2 votes

Given:

f(x) = -3x - 5

g(x) = 4x - 2

Let's find (f + g)(x)

To find (f+g)(x), let's add both functions.

We have:

(f + g)(x) = -3x - 5 + 4x - 2

Collect like terms:

(f + g)(x) = -3x + 4x - 5 - 2

(f + g)(x) = x - 7

ANSWER:

B. (f + g)(x) = x - 7

User Dave Davis
by
5.9k points